Storage and growth temperatures affect growth, flower quality, and bulb quality of Hippeastrum - Chaiartid Inkham (2019)
© 2019, Korean Society for Horticultural Science. The effects of storage and growth temperatures on growth, flower quality, and bulb quality of Hippeastrum sp. were studied. Bulbs of Hippeastrum sp. ‘Apple Blossom’ with circumferences in the range of 22–24 cm were selected and stored for 12 weeks at one of three different temperatures (i.e., room temperature [RT: 30 ± 2 °C], 13 ± 2 °C, and 15 ± 2 °C). After storage, the bulbs were grown in a growth chamber at one of three growth temperatures—that is, RT (30 ± 2 °C), 15 ± 2 °C, and 25 ± 2 °C. The results showed that storing bulbs at RT for 12 weeks reduced their quality in terms of fresh weight, diameter, and firmness, whereas storing bulbs at 13 °C or 15 °C retained their quality in terms of fresh weight and firmness. Electron scanning imaging of the starch granules in the bulb scales showed that prior to storage, the leaf base cells were filled with large starch granules of either lenticular shape or spherical shape. After storing for 12 weeks at RT, the starch granules in the bulb scales were sharply reduced in number and were predominantly of the small, spherical form. A growing temperature of 25 °C could stimulate better growth with respect to plant height, flower diameter, bulb diameter, bulb fresh weight, and bulb dry weight, compared with RT (30 °C). A significant interaction between storage and growing temperatures was found for all parameters except for stalk length. A bulb storage temperature of 15 ± 2 °C for 12 weeks combined with a growing temperature of 25 ± 2 °C produced the best results for both flower and bulb production.